2020
DOI: 10.1182/blood-2020-137742
|View full text |Cite
|
Sign up to set email alerts
|

The Final Analysis of Expand: A Phase 1b, Open-Label, Dose-Finding Study of Ruxolitinib (RUX) in Patients (pts) with Myelofibrosis (MF) and Low Platelet (PLT) Count (50 × 109/L to < 100 × 109/L) at Baseline

Abstract: BACKGROUND RUX, a potent oral JAK1/JAK2 inhibitor, has shown superiority over standard therapies in MF. RUX was approved for the treatment of MF on the basis of the phase 3 COMFORT trials, in which RUX led to sustained improvements in splenomegaly and symptom burden as well as longer survival compared with placebo (COMFORT-I) and best available therapy (COMFORT-II). The starting dose (prescribing information) is based on PLT count: > 200 × 109/L, 20 mg bid; 100-200 × 109/L,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the phase Ib EXPAND study, dose interruptions or reductions were required in 89% of patients who had platelet counts 50-74×10 9 /L, and 78% experienced grade 3 or 4 thrombocytopenia as an adverse event. 12 In the phase IIIb expanded-access JUMP study, 55% of patients who started on ruxolitinib 5 mg BID required further dose reduction, and grade 3 or 4 thrombocytopenia was a common adverse event. 13 There is a significant unmet need for effective and safe therapies for patients living with MF and experiencing severe thrombocytopenia, who may comprise up to 35% of the MF population.…”
Section: Introductionmentioning
confidence: 99%
“…In the phase Ib EXPAND study, dose interruptions or reductions were required in 89% of patients who had platelet counts 50-74×10 9 /L, and 78% experienced grade 3 or 4 thrombocytopenia as an adverse event. 12 In the phase IIIb expanded-access JUMP study, 55% of patients who started on ruxolitinib 5 mg BID required further dose reduction, and grade 3 or 4 thrombocytopenia was a common adverse event. 13 There is a significant unmet need for effective and safe therapies for patients living with MF and experiencing severe thrombocytopenia, who may comprise up to 35% of the MF population.…”
Section: Introductionmentioning
confidence: 99%
“…The 48-week analysis of EXPAND (phase 1b, dose-finding study) in 69 patients with MF and with a baseline platelet count of 50-99 × 10 9 /L, identified a maximum safe starting dose of ruxolitinib 10 mg BID. 28 Similarly, in EXPAND, improvements were observed from baseline to week 24 in spleen and symptom assessments with the 10-mg BID dose. 28 A post hoc analysis of the JUMP study (phase 3b, open-label, single-arm expanded access study)…”
Section: Discussionmentioning
confidence: 87%
“…28 Similarly, in EXPAND, improvements were observed from baseline to week 24 in spleen and symptom assessments with the 10-mg BID dose. 28 A post hoc analysis of the JUMP study (phase 3b, open-label, single-arm expanded access study)…”
Section: Discussionmentioning
confidence: 87%
“…[5][6][7] Thrombocytopenia and anemia events are frequent in patients with MF receiving ruxolitinib and may require treatment dose reductions and discontinuation, which limit efficacy and survival. 13,14,35 Currently, ruxolitinib and fedratinib are not approved for MF patients with severe thrombocytopenia, 8,19 whereas pacritinib approval is limited to patients with platelets <50 × 10 9 /L in the United States. 22 Accelerated approval of pacritinib was based on spleen response in a limited number of patients, and no confirmed symptom benefits are depicted in its label.…”
Section: Discussionmentioning
confidence: 99%